2008
DOI: 10.1038/bjp.2008.72
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium removal augments endothelium‐independent vasodilatation in rat mesenteric vascular bed

Abstract: Background and purpose: The vascular endothelium regulates vascular tone by releasing various endothelium-derived vasoactive substances to counteract excess vascular response. We investigated whether the vascular endothelium regulates vasodilatation via released endothelium-derived contracting factors (EDCFs), by examining the effect of endothelium removal on responses to periarterial nerve stimulation (PNS) and various vasodilator agents. Experimental approach: The rat mesenteric vascular bed was perfused wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
1
19
0
1
Order By: Relevance
“…Our results demonstrated that SNPinduced vasodilation was augmented by L-NAME treatment. We have reported that SNP-induced vasodilation was markedly augmented by L-NAME in the rat mesenteric vascular beds (26). This is due to elimination of NO by L-NAME, leading to increased sensitivity to soluble guanylate cyclase.…”
Section: A23187 (Nmol)mentioning
confidence: 97%
“…Our results demonstrated that SNPinduced vasodilation was augmented by L-NAME treatment. We have reported that SNP-induced vasodilation was markedly augmented by L-NAME in the rat mesenteric vascular beds (26). This is due to elimination of NO by L-NAME, leading to increased sensitivity to soluble guanylate cyclase.…”
Section: A23187 (Nmol)mentioning
confidence: 97%
“…In the experiment using endothelium-denuded preparations, the concentration of methoxamine was reduced to 2 μM, which induced an increase in perfusion pressure to a similar level to that in preparations with an intact endothelium, since endothelium removal enhanced the vasoconstrictor response to methoxamine (16,21).…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…In the experiment using the endotheliumdenuded preparation, the concentration of methoxamine was reduced to 2 μM, which induced an increase in perfusion pressure to a level similar to that in preparations with intact endothelium, since endothelium removal enhanced the vasoconstrictor response to methoxamine (10).…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…The removal and dysfunction of the vascular endothelium have been recognized to augment vasoconstriction induced by various stimulus and vasoactive agonists such as adrenergic nerve stimulation, noradrenaline, and serotonin, suggesting that the endothelium regulates vasoconstriction by releasing EDRF including NO and PGI 2 in the aorta (7 -9). Our recent study demonstrated that the endothelium also regulates vasodilation by releasing EDCF, including vasoconstrictor prostanoids and thromboxane A 2 (10).…”
Section: Introductionmentioning
confidence: 99%